Considering the chemical energy requirements of the tri-n-propylamine co-reactant pathways for the judicious design of new electrogenerated chemiluminescence detection systems. Issue 1 (3rd November 2015) - Kerr, Emily; Doeven, Egan H.; Wilson, David J. D.; Hogan, Conor F.; Francis, Paul S.
Abstract : A simple graphical approach to characterise the energetically feasible electrogenerated chemiluminescence (ECL) reaction pathways with tri- n -propylamine is discussed. Abstract : The introduction of a 'co-reactant' was a critical step in the evolution of electrogenerated chemiluminescence (ECL) from a laboratory curiosity to a widely utilised detection system. In conjunction with a suitable electrochemiluminophore, the co-reactant enables generation of both the oxidised and reduced precursors to the emitting species at a single electrode potential, under the aqueous conditions required for most analytical applications. The most commonly used co-reactant is tri- n -propylamine (TPrA), which was developed for the classic tris(2, 2′-bipyridine)ruthenium(ii ) ECL reagent. New electrochemiluminophores such as cyclometalated iridium(iii ) complexes are also evaluated with this co-reactant. However, attaining the excited states in these systems can require much greater energy than that of tris(2, 2′-bipyridine)ruthenium(ii ), which has implications for the co-reactant reaction pathways. In this tutorial review, we describe a simple graphical approach to characterise the energetically feasible ECL pathways with TPrA, as a useful tool for the development of new ECL detection systems.